HUBUNGAN KADAR HEMOGLOBIN (Hb), INDEKS MASSA TUBUH (IMT) DAN TEKANAN DARAH DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RSUD DOKTER SOEDARSO PONTIANAK BULAN APRIL 2013 - ., Wan Gisca Ayu Astrini (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background.Prevalence of ChronicRenalFailure (CRF) is increasing andbecome a problem in world health. According to National KidneyFoundation (NKF), anemia, malnutritionand hypertension can affect the lifequality of CRF patients who undergoing hemodialysis. Poor life quality canincrease mortality.Purpose.To determine the relationship betweenhemoglobin (Hb) levels, BodyMass Index (BMI)and blood pressure with lifequality of CRF patients who undergoing hemodialysis.Method.Thisresearch was an analytical descriptive study with cross sectional design.The data retrieval is by looking at the medical records of patients. Lifequality was measured by questionnaire WHOQOL-BREF which consistedof 26 questions. Bivariate analysis used Chi-Square test with Fisher testas alternative and multivariate analysis used logisticregression.ResearchResults.Number of samples were 49 people, mostaged between 51-60 years old, most sex were male,Â 43 people (87.8%)were anemia, 6 people (12.2%) were not anemia, 43 people (87.8%) hadunder until normal BMI categorized as malnourished, 6 people (12.2%)had a BMI of over until obese, 45 people (91.8%) had hypertension, 4people (8.2%)had not hypertension and 40 people (81, 6%) had a poorquality of life and 9 people (18.4%) had a good quality of life. There is arelationship between Hb levels with life quality (p = 0.000). The variablethat affect the life quality the most were Hb level (OR= 180,000) and IMT(OR= 36,000).Conclusion.Anemia, malnutrition and hypertension occurred in most HDpatients. Hb levels related to life quality and is the variable that affect themost to life quality of HD patients in RSUD DokterSoedarso Pontianak.Keywords.CRF, HD, life quality, Hb levels, BMI, blood pressure1. Medical EducationProgram, Faculty of Medicine, TanjungpuraUniversity, Pontianak, WestKalimantan.2. Department of Internal Medicine, KharitasBakti Hospital, Pontianak, West Kalimantan.3. Medical Research Unit (MRU), Faculty of Medicine, Tanjungpura University, Pontianak, WestKalimantan.